1989
DOI: 10.1089/aid.1989.5.375
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Expression of Human Immunodeficiency Virus in a Chronically Infected Promonocytic Cell Line by Ultraviolet Irradiation

Abstract: Infection with the human immunodeficiency virus (HIV) is often followed by a prolonged latent state, and mechanisms of maintaining latency or inducing expression from latency are active areas in AIDS research. It has been previously shown using a variety of viruses and cell systems that ultraviolet (UV) irradiation is capable of inducing the expression of latent viruses as well as augmenting the effects of acute viral infection. The ability of UV irradiation to affect HIV latency was investigated using a chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…In other studies, halogenated pyrimidines, UV irradiation, and heat shock have led to virus activation (140,672,1125,1134), perhaps secondary to DNA damage (1210) (Fig. 10).…”
Section: B Monocytesmentioning
confidence: 80%
“…In other studies, halogenated pyrimidines, UV irradiation, and heat shock have led to virus activation (140,672,1125,1134), perhaps secondary to DNA damage (1210) (Fig. 10).…”
Section: B Monocytesmentioning
confidence: 80%
“…Another hypothesis we explored is that MMQO damages DNA and promotes the activation of cytokines or the ATM/ATR response that, through NF-B, could stimulate the HIV-1 promoter. It has been previously described that damaging agents such as UV light may induce the HIV-1 promoter (70,76). We ruled out the participation of ATM/ATR, as an inhibitor of this pathway does not block the stimulating effect of MMQO.…”
Section: Discussionmentioning
confidence: 94%
“…Z. Zmudzka, (unpublished) determined that the HIV promoter can be effectively activated in stably transfected HIVcat/HeLa cells by UVC and UVB, but not UVA radiation. Similarly, UVC and UVB, but not UVA, were found to induce virus expression in a promonocytic cell line chronically infected with HIV (Stanley et al, 1989).…”
Section: Dna Damage Is Neededmentioning
confidence: 92%
“…Its latent form in a human T-cell line, which does not normally produce the virus, was activated by cell exposure to 5'-iododeoxyuridine (IUdR) (Folks et al, 1986). Stanley et al (1989) showed that HIV growth is activated in UVB or UVC irradiated U1 cells, which were chronically infected but supported only a low level of virus production. These authors found that exposures which produced killing of about 25% of the cells are required to produce maximal virus activation.…”
Section: Exposure Of Cells To Uvr Activates Hivmentioning
confidence: 99%
See 1 more Smart Citation